Communication Strategies Used by Pre-Service English Teachers of Different Proficiency Levels - Angela Yicely Castro Garcés; Silvio Fabián López Olivera (Asociación Colombiana de Profesores de Ingles, 2014)
This paper reports on the findings of a research study carried out in the Bachelor of Arts in English program of study at a Colombian university. It aims at identifying the communication strategies used by four pre-service English teachers with A2 and B2 levels of language proficiency and, also, at examining how these communication strategies facilitate or hinder the development of communicative skills. Data collection instruments included audio recordings of three tasks: (1) open-ended questionnaire, (2) sentence translation, and (3) picture description. The participants' speech was transcribed and categorized allowing us to identify and examine the role played by communication strategies which varied depending on the choice the participants made of using either avoidance or compensatory strategies.